2018
DOI: 10.1016/j.immuni.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Fungi Enter the Stage of Colon Carcinogenesis

Abstract: The significant contribution of intestinal bacteria for the pathogenesis of colorectal cancer is widely accepted by now. In this issue of Immunity, two articles by Malik et al. (2018) and Wang et al. (2018) highlight the role of commensal fungi, which so far have been underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
(20 reference statements)
1
18
0
Order By: Relevance
“…The study showed that as fermentation patterns of cellulolytic fungi, Mycoplasma could produce acetate as major metabolites ( Rimoldi et al, 2019 ). However, as no members of Mycoplasma could produce digestive enzymes without symbiotic bacteria ( Conche and Greten, 2018 ), a further study of intestinal symbiosis bacteria is undoubtedly required.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that as fermentation patterns of cellulolytic fungi, Mycoplasma could produce acetate as major metabolites ( Rimoldi et al, 2019 ). However, as no members of Mycoplasma could produce digestive enzymes without symbiotic bacteria ( Conche and Greten, 2018 ), a further study of intestinal symbiosis bacteria is undoubtedly required.…”
Section: Discussionmentioning
confidence: 99%
“…Although these two studies used the same gene-targeted mouse model, the Card9-deficient mice were susceptible to diverse fungal infections. The microbiota difference detected in their mouse models makes the effect of the mycobiota strongly dependent on mouse microbial composition [130]. This further sustains the important role of environmental factors, such as diet, on microbiota composition.…”
Section: Fungal and Viral Contribution To Crc Developmentmentioning
confidence: 69%
“…The significant contribution of gut microorganisms in CRC pathogenesis is widely accepted by now. However, most studies have focused on the role of gut bacteria, underestimating the role of another class of commensals, namely the mycobiota, might also be involved in CRC development [130]. Two recent studies strongly support the role of mycobiota in colitis-associated CRC [131,132].…”
Section: Fungal and Viral Contribution To Crc Developmentmentioning
confidence: 99%
“…In conclusion, fungal dysbiosis is closely linked to the deterioration of colitis to cancer, which reminds us that regulating the state of intestinal mycobiota can be a way to treat colorectal cancer. 76 Irritable bowel syndrome (IBS) IBS has a great impact on human health. The connection with mycobiota was described when it was discovered that the yeast Candida can make allergic patients suffer from IBS.…”
Section: Colorectal Carcinogenesismentioning
confidence: 99%